Pendekatan Resolusi Konflik Dalam Upaya Pencegahan Konflik Regional Pada Era Digitalisasi - Apandi, Apandi (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2020)
Several decades ago, internal conflicts in ASEAN countries became the world's spotlight. Even the impact is very alarming because it causes humanitarian crises, trauma due to armed conflict, violent extremism, and losses to government. Then came the time of international trade tension which had an impact on the economic growth of ASEAN countries. The purpose of this study is to reveal the role of the conflict resolution approach in efforts to prevent regional conflicts in the era of digitalization. Not without reason, the still lack of mutual trust and a less proactive attitude in addressing the situation of conflict between countries made the conflicting ASEAN countries decide to resolve bilaterally or resolve cases to external parties outside ASEAN. The era of digitalization is a hot issue in the trade war and can trigger tension between ASEAN countries. Of course this is not expected, therefore prevention efforts must be made. The literature study method was chosen to examine various findings that support this research to build a strategic model of the importance of the conflict resolution approach in the digitalization era. The results of the study stated that the government must show its credibility and put forward a proactive attitude, ethics in doing business, and building mutual trust and good cooperation between ASEAN countries. A conflict resolution approach can be an alternative to preventing regional conflicts by means of non-violence.